PPARγ agonists as therapeutics for the treatment of Alzheimer’s disease - Landreth, Gary (Springer-Verlag, 2008)
Alzheimer’s disease (AD) is characterized by the deposition of β-amyloid within the brain parenchyma and is accompanied by the impairment of neuronal metabolism and function, leading to extensive neuronal loss. The disease involves the perturbation of synaptic function, energy, and lipid metabolism. The development of amyloid plaques results in the induction of a microglial-mediated inflammatory response. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-activated transcription factor whose biological actions are to regulate glucose and lipid metabolism and suppress inflammatory gene expression. Thus, agonists of this receptor represent an attractive therapeutic target for AD. There is now an extensive body of evidence that has demonstrated the efficacy of PPARγ agonists in ameliorating disease-related pathology and improved learning and memory in animal models of AD. Recent clinical trials of the PPARy agonist rosiglitazone have shown significant improvement in memory and cognition in AD patients. Thus, PPARγ represents an important new therapeutic target in treating AD.